Optimizing ESG Strategy Through ESG Rating Analysis: A Case Study Of PT. X (A State-Owned Enterprise In Indonesia) - Patmanegara, Iqball Dwi Candra; Nainggolan, Yunieta Anny (Integrasi Sains Media, 2025)
This study investigates the strategic function of ESG (Environmental, Social, and Governance) Ratings in enhancing sustainability transformation within PT. X is a leading state-owned enterprise in Indonesia's digital sector. Despite maintaining an